Pesticide exposure and association with physical and hearing symptoms of rural workers - Leusin Mattiazzi, Ângela; Luana Caye, Jaqueline; Gabriela Frank, Jaíne; Denise Endruweit Battisti, Iara (O Mundo da Saúde, 2020)
hearing. The purpose of the study was to characterize rural workers in terms of sociodemographic aspects and exposure to pesticides, as well as to analyze the relationship between this exposure and the occurrence of physical and auditory symptoms. This was a quantitative study, with a descriptive and explanatory scope, using a cross-sectional design, carried out with 71 rural workers, males, exposed to pesticides. Data collection was performed in two ways: (i) a collection instrument for characterizing contact with pesticides, physical and auditory symptoms (ii) auditory screening for the investigation of aerial hearing thresholds. Data analysis was performed through descriptive statistics and through the Wilcoxon test and Spearman’s correlation. The level of significance was set at 5% for statistical tests. Among the physical symptoms associated with the use of pesticides, headaches prevailed (31.0%). As for the result of auditory screenings, 31 (43.7%) rural workers failed in both ears, 28 (39.4%) obtained the results of “passing” and 12 (16.9%) failed in only one ear. When analyzing the association between the results of auditory screenings and variables regarding exposure to pesticides, exposure time was the only variable that showed a significant association. The findings clarify that the professional activity of farmers poses a risk to hearing, however, it is necessary to consider that other factors, such as noise and vibration, can aggravate hearing loss in this population.